Congenital hepatic fibrosis in the Franches-Montagnes horse is associated with the polycystic kidney and hepatic disease 1 (PKHD1) gene. - Michaela Drögemüller; Vidhya Jagannathan; Monika M Welle; Claudia Graubner; Reto Straub; Vinzenz Gerber; Dominik Burger; Heidi Signer-Hasler; Pierre-André Poncet; Stéphane Klopfenstein; Ruedi von Niederhäusern; Jens Tetens; et al. (PLoS ONE, 2014)
Congenital hepatic fibrosis has been described as a lethal disease with monogenic autosomal recessive inheritance in the Swiss Franches-Montagnes horse breed. We performed a genome-wide association study with 5 cases and 12 controls and detected an association on chromosome 20. Subsequent homozygosity mapping defined a critical interval of 952 kb harboring 10 annotated genes and loci including the polycystic kidney and hepatic disease 1 (autosomal recessive) gene (PKHD1). PKHD1 represents an excellent functional candidate as variants in this gene were identified in human patients with autosomal recessive polycystic kidney and hepatic disease (ARPKD) as well as several mouse and rat mutants. Whereas most pathogenic PKHD1 variants lead to polycystic defects in kidney and liver, a small subset of the human ARPKD patients have only liver symptoms, similar to our horses with congenital hepatic fibrosis. The PKHD1 gene is one of the largest genes in the genome with multiple alternative transcripts that have not yet been fully characterized. We sequenced the genomes of an affected foal and 46 control horses to establish a comprehensive list of variants in the critical interval. We identified two missense variants in the PKHD1 gene which were strongly, but not perfectly associated with congenital hepatic fibrosis. We speculate that reduced penetrance and/or potential epistatic interactions with hypothetical modifier genes may explain the imperfect association of the detected PKHD1 variants. Our data thus indicate that horses with congenital hepatic fibrosis represent an interesting large animal model for the liver-restricted subtype of human ARPKD.